On Line Work Control System - Balvinderjeet Singh (My University, 2008)
As a part of the system of MCA, I did online work control project has been developed for the customer service division (CSD). Presently when a customer request and allocating the call to an engr. Is again being done manually, which includes preparing of the service call note (SCN). Once the service is completed the completed scn is entered into the existing scn system and various parameters are calculated relating to the engr. Performance and machine performance for that service call. The online work control system has been has been developed to assist the W/C in getting the machine serviced. The manor modules included in this system are: 1. Call Ligging. A call can be logged on the basis of last four digits of the machine srno. or on the first 3 characters of the customer name. 2. Engineer Allocation This system includes the service analysis being performed by the existing SCN system also. This system is expected to be implemented at about 20 branches, replacing the existing SCN system. This system has been developed in the CLIPPER-87 software package. It is extremely interactive and user friendly. Care has been taken to validate the inputs and flash the error messages suggesting the corrective action. System designing has been done keeping in mind the minimum response time requirement expected from an online system.
Keywords: On Line Work; Work Control; Computer Science and Engineering